Wave absorbers and compounds
Patent Information
- Application Number
- JP2023111034
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-14
- Filing Date
- 2023-07-05
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-03-18
AI Technical Summary
【0013】 本発明の一実施形態によれば、金属層を有しない電波吸収体であって、かつ、ミリ波帯域における透過減衰量及び反射減衰量が共に10dB以上である電波吸収体が提供される。 本発明の他の実施形態によれば、上記電波吸収体の製造に用いられるコンパウンドが提供される。
Smart Images

Figure 0007640621000001 
Figure 0007640621000002 
Figure 0007640621000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to wave absorbers and compounds. [Background technology]
[0002] In recent years, with the diversification of the use of radio waves in high frequency bands, such as in Electronic Toll Collection Systems (ETC), Advanced Cruise-Assist Highway Systems (AHS), and satellite broadcasting, malfunctions and breakdowns of electronic devices due to radio interference have become a problem. In order to reduce the impact of such radio interference on electronic devices, radio wave absorbers are used to absorb unnecessary radio waves and prevent the reflection of radio waves.
[0003] For example, Patent Document 1 discloses a radio wave absorbing sheet having a flexible radio wave absorbing layer containing a particulate radio wave absorbing material and a resin binder, in which the radio wave absorbing material is magnetic iron oxide that magnetically resonates in a frequency band equal to or higher than the millimeter wave band, and the easy axis of magnetization of the radio wave absorbing material is magnetically oriented in one direction within the plane of the radio wave absorbing sheet. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-56492 A Summary of the Invention [Problem to be solved by the invention]
[0005] A radio wave absorber is required to have both high return loss and transmission attenuation, specifically, both of which are required to be 10 dB or more. One method for increasing the return loss of a radio wave absorber is to provide a reflective layer that reflects radio waves on the side of the radio wave absorbing layer opposite to the side where the radio waves are incident (the so-called back side). A layer containing metal (the so-called metal layer) is generally used as the reflective layer, but in recent years, there has been a trend to avoid using metal layers from the viewpoint of recycling. In addition, radio wave absorbers that have a metal layer have problems such as the radio wave absorbing layer and the metal layer being easily peeled off, the metal layer itself being easily deteriorated, and high costs. For this reason, it is desirable to design a radio wave absorber that does not have a metal layer.
[0006] However, in the case of a commonly used dielectric type wave absorber, if no metal layer is provided, the reflection loss decreases when an attempt is made to ensure the transmission loss. In a radio wave absorber that does not have a metal layer, it has conventionally been difficult to improve both the reflection loss and the transmission loss.
[0007] Regarding the above-mentioned points, Patent Document 1 does not pay any attention to the problems that arise when a metal layer is included, and does not mention anything about increasing both the reflection loss and the transmission loss in a radio wave absorber that does not include a metal layer.
[0008] An object of the present invention is to provide a radio wave absorber that does not have a metal layer and has a transmission attenuation and a return attenuation of 10 dB or more in the millimeter wave band. Another object of the present invention is to provide a compound used in the manufacture of the radio wave absorber. [Means for solving the problem]
[0009] Means for solving the above problems include the following aspects. <1> A radio wave absorber having a radio wave absorbing layer containing a magnetic powder and a binder, and not having a metal layer, the filling rate of the magnetic powder in the radio wave absorbing layer is 35 volume % or less; A radio wave absorber that satisfies the relationship 0.65≦(P / 100)×Q, where P is a volume percent of the filling rate of the magnetic powder in the radio wave absorbing layer and Q mm is a thickness of the radio wave absorbing layer. <2> The thickness of the electromagnetic wave absorbing layer is 10 mm or less, and the filling rate is 8 volume % or more and 35 volume % or less. <1> 2. The radio wave absorber according to claim 1 . <3> The thickness of the electromagnetic wave absorbing layer is 5 mm or less, and the filling rate is 15 volume % or more and 35 volume % or less. <1> or <2> 2. The radio wave absorber according to claim 1 . <4> The magnetic powder contains magnetoplumbite-type hexagonal ferrite powder. <1> ~ <3> 13. The radio wave absorber according to claim 12, <5> The magnetic powder contains a powder of magnetoplumbite-type hexagonal ferrite represented by the following formula (1): <1> ~ <4> 13. The radio wave absorber according to claim 12,
[0010] [ka]
[0011] In formula (1), A represents at least one metal element selected from the group consisting of Sr, Ba, Ca, and Pb, and x satisfies 1.5≦x≦8.0.
[0012] <6> In the above formula (1), A is Sr. <5> 2. The radio wave absorber according to claim 1 . <7> In the above formula (1), x satisfies 1.5≦x≦6.0. <5> or <6> 2. The radio wave absorber according to claim 1 . <8> The magnetic powder is measured by the laser diffraction scattering method, and the most frequent value is the mode diameter, and the cumulative 10% diameter is the D 10 , and cumulative 90% diameter is D 90 When the mode diameter is 5 μm or more and less than 10 μm, and (D 90 -D 10 ) / mode diameter ≦ 3.0 <1> ~ <7> 13. The radio wave absorber according to claim 12, <9> Has a planar shape <1> ~ <8> 13. The radio wave absorber according to claim 12, <10> Has a three-dimensional shape <1> ~ <8> 13. The radio wave absorber according to claim 12, <11> <1> ~ <10> 10. A compound used in the manufacture of the radio wave absorber according to any one of claims 1 to 9, comprising a magnetic powder and a binder, and a filling rate of the magnetic powder is 35 volume % or less. Effect of the Invention
[0013] According to one embodiment of the present invention, there is provided a radio wave absorber that does not have a metal layer and has a transmission loss and a return loss of 10 dB or more in the millimeter wave band. According to another embodiment of the present invention, there is provided a compound used in the production of the above-mentioned radio wave absorber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] An example of an embodiment of a radio wave absorber to which the present invention is applied will be described below. However, the present invention is not limited to the following embodiment, and can be practiced with appropriate modifications within the scope of the object of the present invention.
[0015] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of the multiple substances, unless otherwise specified.
[0016] In the present disclosure, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved.
[0017] In this disclosure, the conversion factor from the non-SI unit "Oe" to the SI unit "A / m" is "10 3 / 4π", where π is 3.1416.
[0018] In this disclosure, the non-SI unit "emu" is converted to the SI unit "A·m 2 The conversion factor to -3 "
[0019] [Radio wave absorber] The radio wave absorber of the present disclosure has a radio wave absorbing layer containing a magnetic powder and a binder, and does not have a metal layer, in which the filling rate of the magnetic powder in the radio wave absorbing layer is 35 volume % or less, and when the filling rate of the magnetic powder in the radio wave absorbing layer is P volume %, and the thickness of the radio wave absorbing layer is Q mm, the radio wave absorber satisfies the relationship 0.65≦(P / 100)×Q. The radio wave absorber of the present disclosure has a radio wave absorbing layer containing magnetic powder and a binder, and the filling rate of the magnetic powder in the radio wave absorbing layer is 35 vol % or less. When the filling rate of the magnetic powder in the radio wave absorbing layer is P vol % and the thickness of the radio wave absorbing layer is Q mm, the relationship of 0.65≦(P / 100)×Q is satisfied. Therefore, even though the radio wave absorber does not have a metal layer, both the transmission attenuation and the reflection attenuation in the millimeter wave band are 10 dB or more. A radio wave absorber having a transmission loss and a return loss both of which are 10 dB or more can absorb at least 90% of radio waves.
[0020] ~Composition of radio wave absorber~ The radio wave absorber of the present disclosure is a radio wave absorber that has a radio wave absorbing layer and does not have a metal layer. In the present disclosure, a "metal layer" refers to a layer that contains a metal and that substantially reflects radio waves. Here, "substantially reflects radio waves" means, for example, that 90% or more of the incident radio waves are reflected. The metal layer may be a metal plate, a metal foil, or the like, and may be, for example, a thin metal film formed by vapor deposition. The metal layer is generally formed on the side of the radio wave absorbing layer opposite to the side on which the radio wave is incident. Note that layers that correspond to radio wave absorbing layers are not included in the "metal layer" in this disclosure.
[0021] The wave absorber of the present disclosure may have layers (so-called other layers) other than the wave absorbing layer, if necessary, within the scope that does not impair the effect of the wave absorber of the present disclosure. Examples of the other layers include a protective layer, an adhesive layer, and a release layer. Furthermore, the radio wave absorber of the present disclosure may have a metal-free reflective layer as another layer within the scope of not impairing the effect of the radio wave absorber of the present disclosure, but an embodiment not having a metal-free reflective layer is preferable.
[0022] ~Shape of radio wave absorber~ The radio wave absorber of the present disclosure may have a planar shape or a three-dimensional shape. The planar shape is not particularly limited, and examples thereof include a sheet shape, a film shape, and the like. The three-dimensional shape may be a tube shape (cylindrical, rectangular tube, etc.), a horn shape, a box shape (where one of the faces is open), or the like.
[0023] [Electromagnetic wave absorbing layer] The radio wave absorbing layer includes a magnetic powder and a binder. The components contained in the radio wave absorbing layer will be described in detail later.
[0024] The filling rate of the magnetic powder in the radio wave absorbing layer is 35% by volume or less, preferably 8% by volume or more and 35% by volume or less, more preferably 15% by volume or more and 35% by volume or less, even more preferably 20% by volume or more and 35% by volume or less, and particularly preferably 25% by volume or more and 35% by volume or less. When the filling rate of the magnetic powder in the radio wave absorbing layer is 35 volume % or less, the radio wave absorber can achieve a return loss of 10 dB or more even when it does not have a metal layer.
[0025] The filling rate of the magnetic powder in the electromagnetic wave absorbing layer is a value measured and calculated by the following method using a scanning electron microscope (SEM). The radio wave absorbing layer is cut into pieces measuring 5 mm x 5 mm. The cut radio wave absorbing layer is attached to a stage, and then a cross section is processed in the thickness direction using a focused ion beam (FIB). The processed radio wave absorbing layer is set on the stage so that its cross section is at the top, and then a cross-sectional SEM image with a field of view of 30 μm x 40 μm is obtained using a field emission scanning electron microscope (FE-SEM) under conditions of a voltage of 15 kV and an observation magnification of 3,000 times. The obtained cross-sectional SEM image is binarized to determine the proportion of magnetic powder, and the filling rate of the magnetic powder is calculated. The above operation is carried out five times by changing the cutting position of the electromagnetic wave absorbing layer, and the arithmetic average of the calculated values is regarded as the packing rate of the magnetic powder in the electromagnetic wave absorbing layer. The arithmetic average value is rounded off to one decimal place.
[0026] As the focused ion beam (FIB) device, for example, a high-performance focused ion beam (FIB) device (product name: MI4050) manufactured by Hitachi, Ltd. can be suitably used. However, the focused ion beam (FIB) device is not limited to this. As the field emission scanning electron microscope (FE-SEM), for example, a field emission scanning electron microscope (product name: SU-8220) manufactured by Hitachi, Ltd. can be suitably used. However, the field emission scanning electron microscope (FE-SEM) is not limited to this.
[0027] When the filling rate of the magnetic powder in the radio wave absorbing layer is P volume % and the thickness of the radio wave absorbing layer is Q mm, the radio wave absorbing layer satisfies the relationship of 0.65≦(P / 100)×Q≦Q, preferably satisfies the relationship of 0.65≦(P / 100)×Q≦5.0, more preferably satisfies the relationship of 0.65≦(P / 100)×Q≦3.5, even more preferably satisfies the relationship of 0.65≦(P / 100)×Q≦1.75, and particularly preferably satisfies the relationship of 0.65≦(P / 100)×Q≦1.0. If the relationship 0.65≦(P / 100)×Q is satisfied, the radio wave absorber can achieve a transmission attenuation of 10 dB or more.
[0028] The thickness of the radio wave absorbing layer is not particularly limited as long as it satisfies the above-mentioned relationship "0.65≦(P / 100)×Q". The thickness of the radio wave absorbing layer is, for example, preferably 20 mm or less, more preferably 10 mm or less, and even more preferably 5 mm or less, from the viewpoint of the degree of freedom in the installation location. The lower limit of the thickness of the radio wave absorbing layer is not particularly limited, but is preferably 2 mm or more from the viewpoint of mechanical properties, for example.
[0029] The thickness of the electromagnetic wave absorbing layer is a value measured using a digital length measuring device, and specifically, is the arithmetic average value of measurements taken at nine arbitrarily selected points. As the digital length measuring machine, for example, a digital length measuring machine (product name: Litematic (registered trademark) VL-50A) manufactured by Mitutoyo Corporation can be suitably used. However, the digital length measuring machine is not limited to this.
[0030] As an embodiment that satisfies the relationship 0.65≦(P / 100)×Q, for example, a preferred embodiment is one in which the thickness of the radio wave absorbing layer is 10 mm or less and the filling rate of the magnetic powder in the radio wave absorbing layer is 8 volume % or more and 35 volume % or less, a more preferred embodiment is one in which the thickness of the radio wave absorbing layer is 5 mm or less and the filling rate of the magnetic powder in the radio wave absorbing layer is 15 volume % or more and 35 volume % or less, and a further more preferred embodiment is one in which the thickness of the radio wave absorbing layer is 2 mm or more and 5 mm or less and the filling rate of the magnetic powder in the radio wave absorbing layer is 20 volume % or more and 35 volume % or less.
[0031] <Magnetic powder> The radio wave absorbing layer includes magnetic powder. The magnetic powder is not particularly limited, and examples thereof include powders of ferrite, iron oxide, cobalt, and chromium oxide. From the viewpoint of radio wave absorption performance, the magnetic powder preferably contains magnetoplumbite hexagonal ferrite powder (hereinafter also referred to as "magnetoplumbite hexagonal ferrite powder"), and more preferably is magnetoplumbite hexagonal ferrite powder. Magnetoplumbite-type hexagonal ferrite generally has the composition formula A 1 Fe 12 O 19 (In the formula, A 1 represents a metal element such as Sr, Ba, Ca, or Pb. However, the concept of “magnetoplumbite-type hexagonal ferrite” in this disclosure includes the composition formula A 1 Fe 12 O 19 In addition to the magnetoplumbite hexagonal ferrite represented by the formula (1) below, the magnetoplumbite hexagonal ferrite represented by the formula (1) below is also included. A 1 is preferably at least one metal element selected from the group consisting of Sr, Ba, Ca, and Pb, for example, from the viewpoint of operability and handling.
[0032] The magnetic powder preferably contains a powder of magnetoplumbite-type hexagonal ferrite represented by the following formula (1), for example, in that it has excellent magnetic properties and can exhibit excellent radio wave absorption performance even in the high frequency band, and is preferably a powder of magnetoplumbite-type hexagonal ferrite represented by formula (1). Hereinafter, the magnetoplumbite hexagonal ferrite represented by formula (1) is also referred to as "specific magnetoplumbite hexagonal ferrite." In addition, powder of specific magnetoplumbite hexagonal ferrite is also referred to as "specific magnetoplumbite hexagonal ferrite powder."
[0033] [ka]
[0034] In formula (1), A represents at least one metal element selected from the group consisting of Sr, Ba, Ca, and Pb, and x satisfies 1.5≦x≦8.0.
[0035] As long as A in formula (1) is at least one metal element selected from the group consisting of Sr, Ba, Ca, and Pb, the type and number of the metal element are not particularly limited. In terms of operability and handling, A in formula (1) is preferably at least one metal element selected from the group consisting of Sr, Ba, and Ca. Furthermore, A in formula (1) preferably contains Sr, and more preferably is Sr, in that it can exhibit excellent radio wave absorption performance, for example, around 79 GHz.
[0036] In formula (1), x satisfies 1.5≦x≦8.0, preferably satisfies 1.5≦x≦6.0, more preferably satisfies 1.5≦x≦4.0, and further preferably satisfies 1.5≦x≦3.0. When x in formula (1) is 1.5 or more, radio waves in a frequency band higher than 60 GHz can be absorbed. When x in formula (1) is 8.0 or less, the magnetoplumbite-type hexagonal ferrite has magnetism.
[0037] Specific magnetoplumbite hexagonal ferrites include SrFe (10.44) Al (1.56) O 19 , SrFe (10.00) Al (2.00) O 19 , SrFe (9.95) Al (2.05) O 19 , SrFe (9.85) Al (2.15) O 19 , SrFe (9.79) Al (2.21) O 19 , SrFe (9.74) Al (2.26) O 19 , SrFe (9.70) Al (2.30) O 19 , SrFe(9.58) Al (2.42) O 19 , SrFe (9.37) Al (2.63) O 19 , SrFe (9.33) Al (2.67) O 19 , SrFe (9.27) Al (2.73) O 19 , SrFe (7.88) Al (4.12) O 19 , SrFe (7.71) Al (4.29) O 19 , SrFe (7.37) Al (4.63) O 19 , SrFe (7.04) Al (4.96) O 19 , SrFe (6.25) Al (5.75) O 19 , BaFe (9.50) Al (2.50) O 19 , BaFe (10.05) Al (1.95) O 19 , Cafe (10.00) Al (2.00) O 19 , PbFe (9.00) Al (3.00) O 19 , Sr (0.80) Ba (0.10) Ca (0.10) Fe (9.83) Al (2.17) O 19 , Sr (0.80) Ba (0.10) Ca (0.10) Fe (8.85) Al (3.15) O 19 etc. For example, SrFe (10.00) Al (2.00) O 19 is a specific magnetoplumbite-type hexagonal ferrite with a resonant frequency of around 76.5 GHz, and SrFe (9.70) Al (2.30) O 19 is a specific magnetoplumbite-type hexagonal ferrite having a resonant frequency in the vicinity of 85.0 GHz.
[0038] A method for producing the specific magnetoplumbite-type hexagonal ferrite powder will be described later.
[0039] The composition of the magnetoplumbite-type hexagonal ferrite is confirmed by high-frequency inductively coupled plasma (ICP) emission spectrometry. Specifically, a pressure-resistant container containing 12 mg of sample powder and 10 mL of 4 mol / L (liter; the same applies below) hydrochloric acid solution is kept in an oven set at a temperature of 120°C for 12 hours to obtain a solution. Next, 30 mL of pure water is added to the obtained solution, and then it is filtered using a 0.1 μm membrane filter. The elemental analysis of the filtrate thus obtained is performed using an inductively coupled plasma (ICP) optical emission spectrometer. Based on the results of the elemental analysis obtained, the content of each metal atom relative to 100 atomic % of iron atoms is calculated. The composition is confirmed based on the calculated content. As an ICP optical emission spectrometer, for example, ICPS-8100 (model number) manufactured by Shimadzu Corporation can be suitably used, although the ICP optical emission spectrometer is not limited to this.
[0040] The crystal phase of the magnetoplumbite hexagonal ferrite may or may not be a single phase, but when the magnetoplumbite hexagonal ferrite is a specific magnetoplumbite hexagonal ferrite, the crystal phase is preferably a single phase. A powder of a specific magnetoplumbite-type hexagonal ferrite having a single crystal phase tends to have a higher coercive force and better magnetic properties than a powder of a specific magnetoplumbite-type hexagonal ferrite having a non-single crystal phase (e.g., a two-phase crystal phase) when the aluminum content is the same.
[0041] In the present disclosure, the term "single-phase crystal" refers to a case in which only one type of diffraction pattern showing the crystal structure of magnetoplumbite-type hexagonal ferrite of a given composition is observed in a powder X-ray diffraction (XRD: X-Ray-Diffraction; the same applies below). On the other hand, in the present disclosure, the case where "the crystal phase is not a single phase" refers to a case where a plurality of magnetoplumbite-type hexagonal ferrites of any composition are mixed and two or more types of diffraction patterns are observed, or a diffraction pattern of a crystal other than magnetoplumbite-type hexagonal ferrite is observed.
[0042] When the crystal phase is not a single phase, a diffraction pattern having a main peak and other peaks is obtained. Here, the "main peak" refers to the peak having the highest diffraction intensity in the observed diffraction pattern. When the radio wave absorbing layer contains magnetoplumbite-type hexagonal ferrite powder as the magnetic powder, the ratio (Is / Im) of the diffraction intensity value of the main peak (hereinafter referred to as "Im") to the diffraction intensity value of the other peaks (hereinafter referred to as "Is") obtained by powder X-ray diffraction (XRD) measurement of the magnetoplumbite-type hexagonal ferrite powder is, for example, preferably 1 / 2 or less, and more preferably 1 / 5 or less, from the viewpoint of being able to produce a radio wave absorber having superior radio wave absorbing performance. In addition, when two or more diffraction patterns overlap and each peak of the diffraction pattern has a maximum value, the respective maximum values are defined as Im and Is, and the ratio is calculated. In addition, when two or more diffraction patterns overlap and a peak other than the main peak is observed as a shoulder, the maximum intensity value of the shoulder is defined as Is, and the ratio is calculated. When two or more other peaks are present, the sum of the respective diffraction intensities is defined as Is, and the ratio is calculated.
[0043] For the assignment of diffraction patterns, for example, the database of the International Centre for Diffraction Data (ICDD, registered trademark) can be referenced. For example, the diffraction pattern of magnetoplumbite-type hexagonal ferrite containing Sr can be found in "00-033-1340" of the International Center for Diffraction Data (ICDD). However, when a part of the iron is replaced with aluminum, as in the case of certain magnetoplumbite-type hexagonal ferrites, the peak position shifts.
[0044] As described above, it is confirmed by powder X-ray diffraction (XRD) measurement that the crystal phase of the magnetoplumbite-type hexagonal ferrite is a single phase. Specifically, the measurement is performed using a powder X-ray diffraction (XRD) device under the following conditions. As a powder X-ray diffraction (XRD) device, for example, X'Pert Pro (product name) from PANalytical Corp. can be suitably used, although the powder X-ray diffraction (XRD) device is not limited thereto.
[0045] -conditions- X-ray source: CuKα ray [Wavelength: 1.54 Å (0.154 nm), Output: 40 mA, 45 kV] Scan range: 20°<2θ<70° Scan interval: 0.05° Scan speed: 0.75° / min
[0046] Whether the radio wave absorbing layer contains magnetoplumbite-type hexagonal ferrite powder can be confirmed, for example, by the following method. The electromagnetic wave absorbing layer is finely chopped, soaked in a solvent (e.g., acetone) for 1 to 2 days, and then dried. The dried electromagnetic wave absorbing layer is further ground into fine powder and subjected to powder X-ray diffraction (XRD) measurement to confirm the structure. Moreover, after cutting out a cross section of the radio wave absorbing layer, the composition can be confirmed by using, for example, an energy dispersive X-ray analyzer.
[0047] The shape of the particles constituting the magnetic powder is not particularly limited, and examples thereof include spherical, rod-like, needle-like, flat, and irregular shapes. The shape of the particles constituting the magnetoplumbite type hexagonal ferrite powder may be, for example, flat or irregular.
[0048] The size of the particles constituting the magnetic powder is not particularly limited. The magnetic powder (preferably magnetoplumbite type hexagonal ferrite powder, more preferably specific magnetoplumbite type hexagonal ferrite powder; the same applies below) has a number-based particle size distribution measured by a laser diffraction scattering method, in which the mode diameter is the most frequent value, the cumulative 10% diameter is the D 10 , and cumulative 90% diameter is D 90 When the mode diameter is 5 μm or more and less than 10 μm, and (D 90 -D 10 ) / mode diameter ≦ 3.0, the mode diameter is 5 μm or more and less than 10 μm, and (D 90 -D 10 ) / mode diameter ≦ 2.5, and the mode diameter is 5 μm or more and less than 10 μm, and (D 90 -D 10 It is more preferable that the mode diameter is 5 μm or more and less than 10 μm, and (D 90 -D 10 It is particularly preferable that the mode diameter is 5 μm or more and less than 10 μm, and (D 90 -D 10 ) / mode diameter≦1.0.
[0049] The mode diameter is 5 μm or more, (D 90 -D 10 ) / mode diameter≦3.0, there is a relatively small amount of fine particles with inferior magnetic properties, so that it tends to be possible to produce a radio wave absorber with superior radio wave absorbing performance. The mode diameter is less than 10 μm, (D 90 -D 10 ) / mode diameter≦3.0, there is a tendency that a radio wave absorber having superior strength can be manufactured since there are relatively few coarse particles.
[0050] The particle size of the magnetic powder (i.e., mode diameter, D 10 , and D 90 ) can be controlled by classification using a sieve, a centrifuge, etc., or by pulverization using a mortar and pestle, an ultrasonic disperser, etc. For example, when the particle size of the magnetic powder is controlled by pulverization, it can be adjusted to the desired value by selecting the pulverization means, pulverization time, media material, media diameter, etc. For example, when the magnetic powder is pulverized using media, the particle size of the magnetic powder tends to become smaller. Also, for example, the longer the pulverization time, the smaller the particle size of the magnetic powder tends to become. Also, for example, the smaller the media diameter, the smaller the particle size of the magnetic powder tends to become. "(D 90 -D 10 The value of "(mode diameter) / mode diameter" can be adjusted to a desired value by, for example, sorting the particles by classification using a sieve, a centrifuge, or the like after pulverization.
[0051] The mode, cumulative 10% diameter, and cumulative 90% diameter of the magnetic powder are values determined based on the particle size distribution based on the number of particles measured by a laser diffraction scattering method. Specifically, they are values measured by the following method. 10 mg of magnetic powder is diluted with 500 mL of cyclohexanone, then stirred for 30 seconds using a shaker, and the resulting liquid is used as a sample for particle size distribution measurement. Next, the particle size distribution of the sample for particle size distribution measurement is measured by the laser diffraction scattering method. A laser diffraction / scattering type particle size distribution measurement device is used as the measurement device.
[0052] As the laser diffraction / scattering type particle size distribution measuring device, for example, Partica LA-960 (product name) manufactured by Horiba, Ltd. can be suitably used. However, the laser diffraction / scattering type particle size distribution measuring device is not limited to this.
[0053] The particle size of the magnetic powder contained in the radio wave absorbing layer can be confirmed, for example, by the following method. The electromagnetic wave absorbing layer is finely chopped and then ultrasonically dispersed in a solvent (e.g., acetone). The resulting dispersion is used as a sample and measured by the laser diffraction scattering method to confirm the particle size of the magnetic powder.
[0054] The coercive force (Hc) of the magnetic powder is not particularly limited, but is preferably, for example, 2.5 kOe or more, more preferably 4.0 kOe or more, and even more preferably 5.0 kOe or more. When the coercive force (Hc) of the magnetic powder is 2.5 kOe or more, a radio wave absorber having superior radio wave absorbing performance can be produced. The upper limit of the coercive force (Hc) of the magnetic powder is not particularly limited, but is preferably, for example, 18 kOe or less.
[0055] The saturation magnetization (δs) per unit mass of the magnetic powder is not particularly limited, but is preferably, for example, 10 emu / g or more, more preferably 20 emu / g or more, and even more preferably 30 emu / g or more. When the saturation magnetization (δs) per unit mass of the magnetic powder is 10 emu / g or more, a radio wave absorber with more excellent radio wave absorbing performance can be produced. The upper limit of the saturation magnetization (δs) per unit mass of the magnetic powder is not particularly limited, but is preferably, for example, 60 emu / g or less.
[0056] The coercive force (Hc) and saturation magnetization per unit mass (δs) of the magnetic powder were measured using a vibrating sample magnetometer under conditions of an ambient temperature of 23°C, a maximum applied magnetic field of 50 kOe, and a magnetic field sweep rate of 25 Oe / s (seconds). As the vibrating sample magnetometer, for example, a TM-TRVSM5050-SMSL model (model number) manufactured by Tamagawa Manufacturing Co., Ltd. can be suitably used. However, the vibrating sample magnetometer is not limited to this.
[0057] The radio wave absorbing layer may contain only one type of magnetic powder, or may contain two or more types.
[0058] The content by mass of the magnetic powder in the radio wave absorbing layer is not particularly limited as long as the filling rate of the magnetic powder in the radio wave absorbing layer is 35 volume % or less.
[0059] ~Method of manufacturing specific magnetoplumbite type hexagonal ferrite powder~ The method for producing the specific magnetoplumbite-type hexagonal ferrite powder is not particularly limited. The specific magnetoplumbite-type hexagonal ferrite powder can be produced by either a solid phase method or a liquid phase method. Examples of methods for producing the specific magnetoplumbite type hexagonal ferrite powder by a solid phase method include a method using SrCO3, Al2O3, α-Fe2O3, etc. as raw materials. For a general method for producing the specific magnetoplumbite type hexagonal ferrite powder by a solid phase method, refer to paragraphs
[0023] to
[0025] of Japanese Patent No. 4674380 as appropriate. As a method for producing the specific magnetoplumbite-type hexagonal ferrite powder, the method described below (hereinafter referred to as "production method A") is preferred from the viewpoint of easily obtaining specific magnetoplumbite-type hexagonal ferrite powder having superior magnetic properties.
[0060] Manufacturing method A includes step A of obtaining a reaction product containing Fe, Al, and at least one metal element selected from the group consisting of Sr, Ba, Ca, and Pb (hereinafter also referred to as "specific metal element") by a liquid phase method, step B of drying the reaction product obtained in step A to obtain a dried product, and step C of either a step of firing the dried product obtained in step B to obtain a fired product, and then pulverizing the obtained fired product (hereinafter also referred to as "step c1"), or a step of pulverizing the dried product obtained in step B to obtain a pulverized product, and then firing the obtained pulverized product (hereinafter also referred to as "step c2"). Each of step A, step B, and step C may be divided into two or more stages. Furthermore, the production method A may include steps other than step A, step B, and step C, as necessary. Each step will be described in detail below.
[0061] (Process A) Step A is a step of obtaining a reaction product containing Fe, Al, and at least one metal element (i.e., specific metal element) selected from the group consisting of Sr, Ba, Ca, and Pb, by a liquid phase method. In step A, a reaction product that is a precursor of the specific magnetoplumbite-type hexagonal ferrite powder can be obtained. The reaction product obtained in step A is presumed to be iron hydroxide, aluminum hydroxide, a composite hydroxide of iron, aluminum, and a specific metal element, or the like.
[0062] Step A preferably includes a step of mixing an aqueous solution containing an Fe salt, an Al salt, and a salt of a specific metal element (hereinafter also referred to as a "raw aqueous solution") with an alkaline aqueous solution to obtain a reaction product (hereinafter also referred to as a "step A1"). In step A1, a raw material aqueous solution and an alkaline aqueous solution are mixed to generate a precipitate of a reaction product. In step A1, a liquid containing a reaction product that is a precursor of the specific magnetoplumbite-type hexagonal ferrite powder (so-called a precursor-containing liquid) can be obtained. Moreover, step A preferably includes a step of subjecting the reaction product obtained in step A1 to solid-liquid separation (hereinafter also referred to as "step A2"). In step A2, a reaction product (that is, the reaction product in step A) that serves as a precursor of the specific magnetoplumbite-type hexagonal ferrite powder can be obtained.
[0063] -Process A1- Step A1 is a step of mixing an aqueous solution containing an Fe salt, an Al salt, and a salt of a specific metal element (that is, a raw aqueous solution) with an alkaline aqueous solution to obtain a reaction product. The salts in the Fe salts, Al salts, and salts of specific metal elements are not particularly limited, and from the viewpoints of availability and cost, for example, water-soluble inorganic acid salts such as nitrates, sulfates, and chlorides are preferred. Examples of Fe salts include iron(III) chloride hexahydrate (FeCl3·6H2O) and iron(III) nitrate nonahydrate (Fe(NO3)3·9H2O). Specific examples of aluminum salts include aluminum chloride hexahydrate (AlCl3·6H2O) and aluminum nitrate nonahydrate (Al(NO3)3·9H2O). Specific examples of Sr salts include strontium chloride hexahydrate (SrCl2·6H2O), strontium nitrate (Sr(NO3)2), and strontium acetate 5-hydrate (Sr(CH3COO)2·0.5H2O). Specific examples of Ba salts include barium chloride dihydrate (BaCl2·2H2O), barium nitrate (Ba(NO3)2), and barium acetate ((CH3COO)2Ba). Examples of calcium salts include calcium chloride dihydrate (CaCl2·2H2O), calcium nitrate tetrahydrate (Ca(NO3)2·4H2O), and calcium acetate monohydrate ((CH3COO)2Ca·H2O). Specific examples of Pb salts include lead(II) chloride [PbCl2] and lead(II) nitrate [Pb(NO3)2].
[0064] The alkaline aqueous solution is not particularly limited, and examples thereof include an aqueous sodium hydroxide solution and an aqueous potassium hydroxide solution. The concentration of the alkaline aqueous solution is not particularly limited, and can be, for example, 0.1 mol / L to 10 mol / L.
[0065] The raw material aqueous solution and the alkaline aqueous solution may simply be mixed together. The raw material aqueous solution and the alkaline aqueous solution may be mixed in their entirety at once, or the raw material aqueous solution and the alkaline aqueous solution may be mixed gradually in small amounts. Alternatively, either the raw material aqueous solution or the alkaline aqueous solution may be mixed while adding the other to the other in small amounts. For example, from the viewpoint of reproducibility of the radio wave absorbing performance, it is preferable to gradually mix the raw material aqueous solution and the alkaline aqueous solution little by little. The method for mixing the raw material aqueous solution and the alkaline aqueous solution is not particularly limited, and examples thereof include a method in which the raw material aqueous solution and the alkaline aqueous solution are mixed by stirring. The stirring means is not particularly limited, and a general stirring tool or stirring device can be used.
[0066] The stirring time is not particularly limited as long as the reaction of the components to be mixed is completed, and can be appropriately set depending on the composition of the raw material aqueous solution, the type of stirring tool or stirring device, etc. The temperature when mixing the raw material aqueous solution and the alkaline aqueous solution is, for example, preferably 100°C or lower from the viewpoint of preventing bumping, and more preferably 95°C or lower from the viewpoint of obtaining a good reaction product, and further preferably 15°C or higher and 92°C or lower. The means for adjusting the temperature is not particularly limited, and a general heating device, cooling device, etc. can be used.
[0067] The pH at 25° C. of the aqueous solution obtained by mixing the raw material aqueous solution and the alkaline aqueous solution is preferably 5 to 13, and more preferably 6 to 12, from the viewpoint of making it easier to obtain a reaction product, for example.
[0068] The mixing ratio between the raw aqueous solution and the alkaline aqueous solution is not particularly limited, and can be set to, for example, 0.1 to 10.0 parts by mass of the alkaline aqueous solution per 1 part by mass of the raw aqueous solution.
[0069] -Process A2- Step A2 is a step of subjecting the reaction product obtained in step A1 to solid-liquid separation. The method of solid-liquid separation is not particularly limited, and examples thereof include decantation, centrifugation, and filtration (suction filtration, pressure filtration, etc.). When the method of solid-liquid separation is centrifugation, the conditions of centrifugation are not particularly limited. For example, it is preferable to carry out centrifugation at a rotation speed of 2000 rpm (revolutions per minute; the same applies below) or more for 3 to 30 minutes. In addition, centrifugation may be carried out multiple times.
[0070] (Process B) Step B is a step of drying the reaction product obtained in step A to obtain a dried material (so-called precursor powder). By drying the reaction product obtained in step A before firing, the reproducibility of the electromagnetic wave absorbing performance of the manufactured electromagnetic wave absorber is improved. In addition, by drying the reaction product obtained in step A before pulverization, the particle size distribution of the specific magnetoplumbite-type hexagonal ferrite powder can be easily controlled by pulverization.
[0071] The drying means is not particularly limited, and examples thereof include a dryer such as an oven. The drying temperature is not particularly limited, but is preferably from 50°C to 200°C, and more preferably from 70°C to 150°C, for example. The drying time is not particularly limited, but is preferably 2 to 50 hours, and more preferably 5 to 30 hours.
[0072] (Process C) Step C is either a step of calcining the dried material obtained in step B to obtain a calcined material, and then pulverizing the calcined material obtained (i.e., step c1), or a step of pulverizing the dried material obtained in step B to obtain a pulverized material, and then calcining the pulverized material obtained (i.e., step c2). The dried product obtained in step B is fired to obtain a fired product, and then the fired product is pulverized. Alternatively, the dried product obtained in step B is pulverized to obtain a pulverized product, and then the pulverized product is fired, whereby a specific magnetoplumbite-type hexagonal ferrite powder having a desired particle size can be obtained.
[0073] Step C may be step c1 or step c2. For example, from the viewpoint of making the magnetic properties after sintering more uniform, step C is preferably step c2. When step C is step c2, the fired and pulverized product may be further pulverized.
[0074] The firing can be carried out using a heating device. The heating device is not particularly limited as long as it can heat to the target temperature, and any known heating device can be used. For example, an electric furnace or a baking device uniquely manufactured to suit the production line can be used as the heating device. The firing is preferably carried out in an air atmosphere. The firing temperature is not particularly limited, but is preferably 900°C or higher, more preferably 900°C to 1400°C, and even more preferably 1000°C to 1200°C, for example. The firing time is not particularly limited, but is preferably 1 hour to 10 hours, and more preferably 2 hours to 6 hours.
[0075] The pulverizing means is not particularly limited as long as it is possible to obtain a specific magnetoplumbite-type hexagonal ferrite powder having a desired particle size. Examples of the grinding means include a mortar and pestle, a grinding machine (a cutter mill, a ball mill, a bead mill, a roller mill, a jet mill, a hammer mill, an attritor, etc.), and the like.
[0076] In the case of pulverization using media, the particle size of the media (so-called media diameter) is not particularly limited, and is, for example, preferably 0.1 mm to 5.0 mm, and more preferably 0.5 mm to 3.0 mm. In the present disclosure, the term "media diameter" refers to the diameter of the media (e.g., beads) in the case of spherical media (e.g., spherical beads), and refers to the diameter obtained by measuring the equivalent circle diameters of multiple media (e.g., beads) from images observed with a transmission electron microscope (TEM) or scanning electron microscope (SEM) and arithmetically averaging the measured values in the case of non-spherical media (e.g., non-spherical beads).
[0077] The material of the media is not particularly limited, and for example, media made of glass, alumina, steel, zirconia, ceramic, etc. can be suitably used.
[0078] <Binder> The electromagnetic wave absorbing layer includes a binder. Examples of binders include thermoplastic resins and thermosetting resins. Examples of thermoplastic resins include acrylic resins, polyacetal, polyamide, polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polystyrene, polyphenylene sulfide, polyvinyl chloride, ABS (acrylonitrile butadiene styrene) resin obtained by copolymerization of acrylonitrile, butadiene, and styrene, and AS (acrylonitrile styrene) resin obtained by copolymerization of acrylonitrile and styrene. Examples of the thermosetting resin include phenol resin, epoxy resin, melamine resin, urea resin, unsaturated polyester, diallyl phthalate resin, urethane resin, and silicone resin.
[0079] An example of the binder is rubber. As the rubber, from the viewpoint of being able to produce a radio wave absorber that has good mixability with the magnetic powder and is superior in durability, weather resistance, and impact resistance, for example, preferred are butadiene rubber; isoprene rubber; chloroprene rubber; halogenated butyl rubber; fluororubber; urethane rubber; acrylic rubber (ACM) obtained by copolymerization of an acrylic acid ester (e.g., ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate) with other monomers; ethylene-propylene rubber obtained by coordination polymerization of ethylene and propylene using a Ziegler catalyst; butyl rubber (IIR) obtained by copolymerization of isobutylene and isoprene; styrene butadiene rubber (SBR) obtained by copolymerization of butadiene and styrene; acrylonitrile butadiene rubber (NBR) obtained by copolymerization of acrylonitrile and butadiene; silicone rubber, and the like.
[0080] Binders also include, for example, thermoplastic elastomers (TPEs). Examples of the thermoplastic elastomer include an olefin-based thermoplastic elastomer (TPO), a styrene-based thermoplastic elastomer (TPS), an amide-based thermoplastic elastomer (TPA), and a polyester-based thermoplastic elastomer (TPC).
[0081] When the radio wave absorbing layer contains rubber as a binder, it may contain various additives such as a vulcanizing agent, a vulcanization aid, a softener, and a plasticizer in addition to the rubber. The vulcanizing agent includes sulfur, organic sulfur compounds, metal oxides, and the like.
[0082] The melt mass slow rate (hereinafter also referred to as "MFR") of the binder is not particularly limited, but for example, it is preferably 1 g / 10 min to 200 g / 10 min, more preferably 3 g / 10 min to 100 g / 10 min, further preferably 5 g / 10 min to 80 g / 10 min, and particularly preferably 10 g / 10 min to 50 g / 10 min. When the MFR of the binder is 1 g / 10 min or more, the fluidity is sufficiently high and poor appearance is less likely to occur. When the MFR of the binder is 200 g / 10 min or less, the mechanical properties such as the strength of the molded body can be easily improved. The MFR of the binder is a value measured in accordance with JIS K 7210:1999 under conditions of a measurement temperature of 230° C. and a load of 10 kg.
[0083] The hardness of the binder is not particularly limited, but from the viewpoint of moldability, for example, it is preferably 5 g to 150 g, more preferably 10 g to 120 g, even more preferably 30 g to 100 g, and particularly preferably 40 g to 90 g. The hardness of the binder is an instantaneous value measured in accordance with JIS K 6253-3:2012.
[0084] The density of the binder is not particularly limited, but is preferably 600 kg / m from the viewpoint of moldability. 3 ~1100kg / m 3It is preferable that the thickness is 700 kg / m 3 ~1000kg / m 3 More preferably, it is 750 kg / m 3 ~1050kg / m 3 More preferably, it is 800 kg / m 3 ~950kg / m 3 It is particularly preferred that: The density of the binder is a value measured in accordance with JIS K 0061:2001.
[0085] The 100% tensile stress of the binder is not particularly limited, but from the viewpoint of moldability, for example, it is preferably 0.2 MPa to 20 MPa, more preferably 0.5 MPa to 10 MPa, even more preferably 1 MPa to 5 MPa, and particularly preferably 1.5 MPa to 3 MPa. The tensile strength of the binder is not particularly limited, but from the viewpoint of moldability, it is preferably from 1 MPa to 20 MPa, more preferably from 2 MPa to 15 MPa, even more preferably from 3 MPa to 10 MPa, and particularly preferably from 5 MPa to 8 MPa. The elongation at break of the binder is not particularly limited, but from the viewpoint of moldability, for example, it is preferably 110% to 1500%, more preferably 150% to 1000%, even more preferably 200% to 900%, and particularly preferably 400% to 800%. The above tensile properties are values measured in accordance with JIS K 6251: 2010. The measurements are performed using JIS No. 3 dumbbells as test pieces at a tensile speed of 500 mm / min.
[0086] The radio wave absorbing layer may contain only one type of binder, or may contain two or more types of binder.
[0087] The filling rate of the binder in the radio wave absorbing layer is not particularly limited, but is preferably, for example, 65 vol. % or more, more preferably 65 vol. % or more and 92 vol. % or less, and even more preferably 65 vol. % or more and 85 vol. % or less.
[0088] <Other additives> The radio wave absorbing layer may contain, in addition to the magnetic powder and binder, various additives (so-called other additives) as necessary within the range that does not impair the effect of the radio wave absorber of the present disclosure. Examples of the other additives include dispersants, dispersion aids, antifungal agents, antistatic agents, antioxidants, etc. The other additives may be ones in which one component has two or more functions.
[0089] [Method of manufacturing radio wave absorber] The method for producing the radio wave absorber of the present disclosure is not particularly limited. The wave absorber of the present disclosure can be produced by a known method using magnetic powder, a binder, and, as necessary, a solvent, other additives, and the like.
[0090] The wave absorber of the present disclosure can be produced, for example, by the following method X. A mixture containing magnetic powder, a binder, and other additives as necessary is kneaded with a kneader while heating to obtain a compound. The compound obtained is then molded to produce a radio wave absorber consisting of a radio wave absorbing layer.
[0091] The magnetic powder in method X is the same as the magnetic powder explained in the section "radio wave absorber", and the preferred embodiments are also the same, so explanation is omitted here. The content of the magnetic powder in the mixture may be adjusted so that the packing rate of the magnetic powder in the finally obtained radio wave absorbing layer is 35 volume % or less.
[0092] The binder in method X has the same meaning as the binder explained in the section "radio wave absorber", and the preferred embodiments are also the same, so the explanation will be omitted here. The binder content in the mixture is not particularly limited, but for example, it is preferable to adjust the binder filling rate in the finally obtained electromagnetic wave absorbing layer to the above-mentioned binder filling rate in the electromagnetic wave absorbing layer.
[0093] The other additives in method X are the same as those explained in the section "radio wave absorber", and preferred embodiments are also the same, so explanation thereof will be omitted here.
[0094] In the mixture, the magnetic powder and the binder may simply be mixed together. The method for mixing the magnetic powder and the binder is not particularly limited, and may be, for example, a method in which they are mixed by stirring. The stirring means is not particularly limited, and a general stirring device can be used. Examples of the stirring device include a paddle mixer and an impeller mixer. The stirring time is not particularly limited and can be appropriately set depending on, for example, the type of stirring device, the composition of the mixture, and the like.
[0095] The heating temperature of the mixture is not particularly limited and can be appropriately set depending on, for example, the type of binder. The heating temperature is preferably a temperature at which the binder can be melted, and can be, for example, 170°C to 300°C.
[0096] The kneading means is not particularly limited, and a general kneading device can be used. Examples of the kneading device include a mixer, a two-roll mill, a kneader, and the like. The kneading conditions are not particularly limited and can be appropriately set depending on, for example, the type of kneading device, the composition of the mixture, and the like.
[0097] Examples of the molding process include press molding, extrusion molding, injection molding, in-mold molding, and molding using a three-dimensional modeling machine. The molding conditions are not particularly limited, and can be appropriately set depending on, for example, the type of molding device, the composition of the mixture, the thickness of the radio wave absorbing layer, and the like.
[0098] The thickness of the radio wave absorbing layer is not particularly limited as long as it satisfies the relationship 0.65≦(P / 100)×Q, where P volume % is the filling rate of the magnetic powder in the radio wave absorbing layer and Q mm is the thickness of the radio wave absorbing layer. The thickness of the electromagnetic wave absorbing layer can be adjusted, for example, by molding the compound.
[0099] Moreover, the wave absorber of the present disclosure can be produced by, for example, the following method Y. A composition for forming a radio wave absorbing layer, which contains a magnetic powder, a binder, and, if necessary, a solvent, other additives, etc., is applied onto a temporary support to form a coating film of the composition for forming a radio wave absorbing layer. The coating film of the composition for forming a radio wave absorbing layer is then dried to form a radio wave absorbing layer. The temporary support is then peeled off from the radio wave absorbing layer to produce a radio wave absorber made of the radio wave absorbing layer.
[0100] The magnetic powder in method Y is the same as the magnetic powder explained in the section "radio wave absorber", and the preferred embodiments are also the same, so explanation is omitted here. The content of the magnetic powder in the composition for forming an electromagnetic wave absorbing layer may be adjusted so that the filling rate of the magnetic powder in the finally obtained electromagnetic wave absorbing layer is 35 volume % or less.
[0101] The binder in method Y has the same meaning as the binder explained in the section "radio wave absorber", and the preferred embodiments are also the same, so the explanation will be omitted here. The binder content in the composition for forming an electromagnetic wave absorbing layer is not particularly limited. For example, it is preferable to adjust the binder filling rate in the finally obtained electromagnetic wave absorbing layer to the binder filling rate in the electromagnetic wave absorbing layer described above.
[0102] The solvent in method Y is not particularly limited, and examples thereof include water, an organic solvent, or a mixed solvent of water and an organic solvent. Examples of the organic solvent include alcohols such as methanol, ethanol, n-propanol, i-propanol, and methoxypropanol; ketones such as acetone, methyl ethyl ketone, cyclohexane, and cyclohexanone; tetrahydrofuran, acetonitrile, ethyl acetate, and toluene.
[0103] When the composition for forming an electromagnetic wave absorbing layer contains a solvent, the content of the solvent in the composition for forming an electromagnetic wave absorbing layer is not particularly limited and can be appropriately set depending on, for example, the types and amounts of components blended in the composition for forming an electromagnetic wave absorbing layer.
[0104] The other additives in method Y have the same meaning as the other additives explained in the section "radio wave absorber", and preferred embodiments are also the same, so explanation thereof will be omitted here.
[0105] In the composition for forming an electromagnetic wave absorbing layer, the magnetic powder and the binder may simply be mixed together. The method for mixing the magnetic powder and the binder is not particularly limited, and may be, for example, a method in which they are mixed by stirring. The stirring means is not particularly limited, and a general stirring device can be used. Examples of the stirring device include a paddle mixer and an impeller mixer. The stirring time is not particularly limited, and can be appropriately set depending on, for example, the type of stirring device, the composition of the radio wave absorbing layer-forming composition, and the like.
[0106] The temporary support is not particularly limited. Examples of the temporary support include a metal plate (a plate of a metal such as aluminum, zinc, or copper), a glass plate, and a plastic sheet (such as a sheet of polyester (polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, or the like), polyethylene (linear low-density polyethylene, low-density polyethylene, high-density polyethylene, or the like), polypropylene, polystyrene, polycarbonate, polyimide, polyamide, polyamideimide, polysulfone, polyvinyl chloride, polyacrylonitrile, polyphenylene sulfide, polyetherimide, polyethersulfone, polyvinyl acetal, acrylic resin, or the like). The surface of the plastic sheet is preferably subjected to a release treatment.
[0107] The size of the temporary support is not particularly limited, and can be appropriately set depending on, for example, the size of the radio wave absorbing layer.
[0108] The thickness of the temporary support is not particularly limited and is usually about 0.01 mm to 0.5 mm, and from the viewpoint of workability, it is preferably 0.05 mm to 0.2 mm, for example.
[0109] The method for applying the composition for forming an electromagnetic wave absorbing layer onto the temporary support is not particularly limited, and examples thereof include methods using a die coater, a knife coater, an applicator, or the like.
[0110] The method for drying the coating film of the composition for forming an electromagnetic wave absorbing layer is not particularly limited, and examples thereof include a method using a heating device such as an oven. The drying temperature and drying time are not particularly limited as long as they can volatilize the solvent contained in the coating film of the composition for forming an electromagnetic wave absorbing layer. For example, the mixture is heated at 70° C. to 90° C. for 1 to 3 hours.
[0111] The thickness of the radio wave absorbing layer is not particularly limited as long as it satisfies the relationship 0.65≦(P / 100)×Q, where P volume % is the filling rate of the magnetic powder in the radio wave absorbing layer and Q mm is the thickness of the radio wave absorbing layer. The thickness of the radio wave absorbing layer can be adjusted, for example, by the amount of the radio wave absorbing layer-forming composition applied.
[0112] [Compound] The compound of the present disclosure is a compound used for producing the radio wave absorber of the present disclosure, which contains magnetic powder and a binder, and has a filling rate of the magnetic powder of 35 volume % or less.
[0113] The magnetic powder in the compound of the present disclosure is the same as the magnetic powder explained in the section "radio wave absorber", and the preferred embodiments are also the same, so the explanation will be omitted here.
[0114] The filling rate of the magnetic powder in the compound of the present disclosure is 35% by volume or less, preferably 8% by volume or more and 35% by volume or less, more preferably 15% by volume or more and 35% by volume or less, and even more preferably 20% by volume or more and 35% by volume or less.
[0115] The filling rate of the magnetic powder in the compound of the present disclosure is a value measured by the following method. A radio wave absorbing layer is produced using the compound of the present disclosure. Using the produced radio wave absorbing layer, the filling rate of the magnetic powder in the radio wave absorbing layer is measured in the same manner as described in the section "Radio wave absorber."
[0116] The binder in the compound of the present disclosure has the same meaning as the binder explained in the section "radio wave absorber", and preferred embodiments are also the same, so explanation thereof will be omitted here.
[0117] The binder filling rate in the compound of the present disclosure is not particularly limited, but is, for example, preferably 65 vol% or more, more preferably 65 vol% or more and 92 vol% or less, and even more preferably 65 vol% or more and 85 vol% or less.
[0118] The compounds of the present disclosure may be in pellet form. The size (diameter) of the pellet-like compound is not particularly limited, but is, for example, preferably 0.5 mm to 20 mm, more preferably 1 mm to 10 mm, further preferably 2 mm to 8 mm, and particularly preferably 3 mm to 6 mm. The density of the pellet-shaped compound is not particularly limited, but is, for example, 500 kg / m 3 ~5000kg / m 3 It is preferable that the thickness is 800 kg / m 3 ~4000kg / m 3 More preferably, it is 1000 kg / m 3 ~3500kg / m 3 More preferably, it is 1200 kg / m 3 ~3000kg / m 3 It is particularly preferred that: The density of the compound is a value measured in accordance with JIS K 0061:2001.
[0119] The compound of the present disclosure may contain various additives (so-called other additives) in addition to the magnetic powder and binder, if necessary. The other additives in the compound of the present disclosure are the same as those described in the section "radio wave absorber", and preferred embodiments are also the same, so description thereof will be omitted here. EXAMPLES
[0120] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.
[0121] [Magnetic powder preparation] [Magnetic powder 1] A raw material aqueous solution prepared by dissolving 57.0 g of iron(III) chloride hexahydrate [FeCl3·6H2O], 27.8 g of strontium chloride hexahydrate [SrCl2·6H2O], and 10.2 g of aluminum chloride hexahydrate [AlCl3·6H2O] in 216.0 g of water was added to 400.0 g of water kept at 35°C at a flow rate of 10 mL / min at the same time to obtain a first liquid. The raw material aqueous solution was prepared by dissolving 57.0 g of iron(III) chloride hexahydrate [FeCl3·6H2O], 27.8 g of strontium chloride hexahydrate [SrCl2·6H2O], and 10.2 g of aluminum chloride hexahydrate [AlCl3·6H2O] in 216.0 g of water. The same solution was added to 181.3 g of 5 mol / L sodium hydroxide aqueous solution by adding 113.0 g of water. The first liquid was obtained by adding the whole amount of the raw material aqueous solution to 181.3 g of 5 mol / L sodium hydroxide aqueous solution at the same time. The whole amount of the raw material aqueous solution was added to the stirred water at a flow rate of 10 mL / min at the same time to obtain a first liquid. Next, the temperature of the first liquid was changed to 25°C, and then 39.8 g of 1 mol / L aqueous sodium hydroxide solution was added while maintaining the temperature to obtain a second liquid. The pH of the obtained second liquid was 10.5. The pH of the second liquid was measured using a tabletop pH meter F-71 (product name) manufactured by Horiba Ltd. (hereinafter the same). Next, the second liquid was stirred for 15 minutes to terminate the reaction, thereby obtaining a liquid containing a reaction product that would become a precursor of the magnetoplumbite-type hexagonal ferrite powder (ie, a precursor-containing liquid). Next, the precursor-containing liquid was subjected to centrifugal separation (rotation speed: 3000 rpm, rotation time: 10 minutes) three times, and the resulting precipitate was collected. Next, the collected precipitate was dried in an oven with an internal atmosphere temperature of 95° C. for 12 hours to obtain an aggregate of particles made of the precursor (i.e., precursor powder). Next, the precursor powder was placed in a muffle furnace, and the temperature inside the furnace was set to 1100° C. in an air atmosphere, and the powder was fired for 4 hours to obtain a fired body. Next, the obtained fired body was pulverized for 90 seconds using a Wonder Crusher WC-3 (product name) manufactured by Osaka Chemical Co., Ltd. with the variable speed dial set to "5," thereby obtaining magnetic powder 1.
[0122] [Magnetic powder 2] A raw material aqueous solution prepared by dissolving 57.0 g of iron(III) chloride hexahydrate [FeCl3·6H2O], 27.8 g of strontium chloride hexahydrate [SrCl2·6H2O], and 10.2 g of aluminum chloride hexahydrate [AlCl3·6H2O] in 216.0 g of water was added to 400.0 g of water kept at 35°C at a flow rate of 10 mL / min at the same time to obtain a first liquid. The raw material aqueous solution was prepared by dissolving 57.0 g of iron(III) chloride hexahydrate [FeCl3·6H2O], 27.8 g of strontium chloride hexahydrate [SrCl2·6H2O], and 10.2 g of aluminum chloride hexahydrate [AlCl3·6H2O] in 216.0 g of water. The same solution was added to 181.3 g of 5 mol / L sodium hydroxide aqueous solution by adding 113.0 g of water. The first liquid was obtained by adding the whole amount of the raw material aqueous solution to 181.3 g of 5 mol / L sodium hydroxide aqueous solution at the same time. The whole amount of the raw material aqueous solution was added to the stirred water at a flow rate of 10 mL / min at the same time to obtain a first liquid. Next, the temperature of the first liquid was changed to 25° C., and then 30.2 g of a 1 mol / L aqueous sodium hydroxide solution was added while maintaining the temperature to obtain a second liquid. The pH of the obtained second liquid was measured and found to be 9.5. Next, the second liquid was stirred for 15 minutes to terminate the reaction, thereby obtaining a liquid containing a reaction product that would become a precursor of the magnetoplumbite-type hexagonal ferrite powder (ie, a precursor-containing liquid). Next, the precursor-containing liquid was subjected to centrifugal separation (rotation speed: 3000 rpm, rotation time: 10 minutes) three times, and the resulting precipitate was collected. Next, the collected precipitate was dried in an oven with an internal atmosphere temperature of 95° C. for 12 hours to obtain an aggregate of particles made of the precursor (i.e., precursor powder). Next, the precursor powder was placed in a muffle furnace, and the temperature inside the furnace was set to 1100° C. in an air atmosphere, and the powder was fired for 4 hours to obtain a fired body. Next, the obtained fired body was pulverized for 60 seconds using a Wonder Crusher WC-3 (product name) manufactured by Osaka Chemical Co., Ltd. with the variable speed dial set to "5," thereby obtaining magnetic powder 2.
[0123] <Confirmation of crystal structure> The crystal structures of the magnetic bodies forming the magnetic powders 1 and 2 (hereinafter also referred to as "magnetic body 1" and "magnetic body 2") were confirmed by X-ray diffraction (XRD). Specifically, it was confirmed whether the material had a magnetoplumbite type crystal structure and whether it was a single phase or had two or more different crystal phases. The measurement was performed using a powder X-ray diffraction device, X'Pert Pro (product name) manufactured by PANalytical Co. The measurement conditions are as follows:
[0124] -Measurement conditions- X-ray source: CuKα ray [Wavelength: 1.54 Å (0.154 nm), Output: 40 mA, 45 kV] Scan range: 20°<2θ<70° Scan interval: 0.05° Scan speed: 0.75° / min
[0125] As a result, it was confirmed that both Magnetic Body 1 and Magnetic Body 2 have a magnetoplumbite crystal structure and are single-phase magnetoplumbite hexagonal ferrites that do not contain any crystal structure other than magnetoplumbite.
[0126] <Confirmation of composition> The composition of each of the magnetic bodies, magnetic body 1 and magnetic body 2, was confirmed by high-frequency inductively coupled plasma (ICP) emission spectrometry. Specifically, this was confirmed by the following method. A beaker (pressure-resistant container) containing 12 mg of magnetic powder and 10 mL of 4 mol / L hydrochloric acid solution was kept in an oven set at 120°C for 12 hours to obtain a solution. 30 mL of pure water was added to the obtained solution, and then filtered using a 0.1 μm membrane filter. Elemental analysis of the filtrate thus obtained was performed using a high-frequency inductively coupled plasma (ICP) optical emission spectrometer (model number: ICPS-8100, Shimadzu Corporation). Based on the results of the elemental analysis, the content of each metal atom relative to 100 atomic % of iron atoms was calculated. Based on the content obtained, the composition of the magnetic material was confirmed. The composition of each magnetic material is shown below.
[0127] Magnetic material 1: SrFe (10.00) Al (2.00) O 19 Magnetic material 2: SrFe (9.70) Al (2.30) O19
[0128] As a result, it was confirmed that both the magnetic powder 1 and the magnetic powder 2 were magnetoplumbite hexagonal ferrite powders represented by formula (1) (that is, specific magnetoplumbite hexagonal ferrite powders).
[0129] <Measurement of particle size distribution> The number-based particle size distribution of each of the magnetic powders, Magnetic Powder 1 and Magnetic Powder 2, was measured by a laser diffraction scattering method to determine the mode (so-called mode diameter), cumulative 10% diameter, and cumulative 90% diameter. Specifically, 10 mg of magnetic powder was diluted with 500 mL of cyclohexanone, and then stirred for 30 seconds using a shaker, and the resulting liquid was used as a sample for particle size distribution measurement. Next, the particle size distribution of the sample for particle size distribution measurement was measured using a laser diffraction / scattering type particle size distribution measuring device (product name: Partica LA-960, Horiba, Ltd.). Based on the obtained particle size distribution based on the number of particles, the mode diameter (unit: μm), which is the most frequent value, and the cumulative 10% diameter D 10 (unit: μm), and cumulative 90% diameter D 90 (Unit: μm) was also calculated. 90 -D 10 ) / mode diameter" was calculated.
[0130] As a result, the magnetic powder 1 had a mode diameter of 6.7 μm and D 10 is 4.1 μm, and D 90 is 9.5μm, and "(D 90 -D 10 The value of "mode diameter" was 0.81. The magnetic powder 2 had a mode diameter of 8.8 μm and a D 10 is 5.5 μm, and D 90 is 12.5μm, and "(D 90 -D 10 ) / mode diameter" was 0.80.
[0131] <Measurement of magnetic properties> For each of the magnetic powders, magnetic powder 1 and magnetic powder 2, the coercive force (Hc) and saturation magnetization (δs) were measured as magnetic properties. Specifically, the measurements were carried out in the following manner. A vibrating sample magnetometer (model: TM-TRVSM5050-SMSL, Tamagawa Manufacturing Co., Ltd.) was used as the measuring device to measure the magnetization strength of the magnetic powder against the applied magnetic field under the conditions of an ambient temperature of 23°C, a maximum applied magnetic field of 50 kOe, and a magnetic field sweep rate of 25 Oe / s (seconds). From the measurement results, the magnetic field (H)-magnetization (M) curve of the magnetic powder was obtained. Based on the obtained magnetic field (H)-magnetization (M) curve, the coercive force (Hc) (unit: kOe) and saturation magnetization (δs) (unit: emu / g) of the magnetic powder were calculated.
[0132] As a result, magnetic powder 1 had a coercive force (Hc) of 10.5 kOe and a saturation magnetization (δs) of 43.2 emu / g, while magnetic powder 2 had a coercive force (Hc) of 10.0 kOe and a saturation magnetization (δs) of 40.2 emu / g.
[0133] [Preparation of radio wave absorber (1)] Example 1 1. Preparation of the compound A compound was prepared using magnetic powder 1 and a binder (product name: Mirastomer (registered trademark) 7030NS, olefin-based thermoplastic elastomer (TPO), Mitsui Chemicals, Inc.) Specifically, the compound was prepared as follows. The magnetic powder 1 and the binder were mixed to obtain a mixture. The amounts of the magnetic powder 1 and the binder were set so that the filling rate of the magnetic powder 1 in the final compound was 15% by volume. The mixture was then kneaded for 20 minutes using a Labo Plastomill (product name, Toyo Seiki Seisakusho Co., Ltd.) at a set temperature of 200°C and a rotation speed of 50 rpm to obtain a compound.
[0134] 2. Preparation of radio wave absorber The obtained compound was molded using a hot press under the conditions of molding pressure: 20 MPa, press temperature: 200°C, and press time: 10 minutes to obtain a sheet-shaped electromagnetic wave absorber (size: 100 mm x 100 mm). The amount of the compound used was set so that the thickness of the finally obtained electromagnetic wave absorber would be 4.5 mm.
[0135] Example 2 The same operations as in Example 1 were carried out to obtain a sheet-shaped radio wave absorber (size: 100 mm x 100 mm), except that the amounts of magnetic powder 1 and the binder were changed so that the filling rate of magnetic powder 1 in the final compound would be 30 volume %, and that the amount of compound used was changed so that the final radio wave absorber would have a thickness of 3 mm.
[0136] Comparative Example 1 Except for changing the amount of the compound used to an amount such that the thickness of the finally obtained radio wave absorber was 3 mm, the same operation as in Example 1 was carried out to obtain a sheet-shaped radio wave absorber (size: 100 mm × 100 mm).
[0137] Comparative Example 2 The same operations as in Example 1 were carried out to obtain a sheet-shaped radio wave absorber (size: 100 mm x 100 mm), except that the amounts of magnetic powder 1 and the binder were changed so that the filling rate of the magnetic powder 1 in the final compound would be 30 volume %, and that the amount of compound used was changed so that the final radio wave absorber would have a thickness of 2 mm.
[0138] Comparative Example 3 The same operations as in Example 1 were carried out to obtain a sheet-shaped radio wave absorber (size: 100 mm x 100 mm), except that the amounts of magnetic powder 1 and the binder were changed so that the filling rate of magnetic powder 1 in the final compound was 40 volume %, and the amount of compound used was changed so that the final radio wave absorber had a thickness of 2 mm.
[0139] Comparative Example 4 The same operations as in Example 1 were carried out to obtain a sheet-shaped radio wave absorber (size: 100 mm x 100 mm), except that the amounts of magnetic powder 1 and the binder were changed so that the filling rate of magnetic powder 1 in the final compound was 40 volume %, and the amount of compound used was changed so that the final radio wave absorber had a thickness of 3 mm.
[0140] Comparative Example 5 The same operations as in Example 1 were carried out to obtain a sheet-shaped radio wave absorber (size: 100 mm x 100 mm), except that the amounts of magnetic powder 1 and the binder were changed so that the filling rate of magnetic powder 1 in the final compound was 50 volume %, and the amount of compound used was changed so that the final radio wave absorber had a thickness of 2 mm.
[0141] Table 1 shows the "filling rate (unit: volume %) of the magnetic powder in the radio wave absorbing layer," "thickness (unit: mm) of the radio wave absorbing layer," and "(P / 100)×Q" of each of the radio wave absorbers in Example 1, Example 2, and Comparative Examples 1 to 5.
[0142] [Preparation of radio wave absorber (2)] Example 3 1. Preparation of the compound A compound was prepared using the magnetic powder 2 and a binder (product name: Mirastomer (registered trademark) 7030NS, olefin-based thermoplastic elastomer (TPO), Mitsui Chemicals, Inc.). Specifically, the compound was prepared as follows. The magnetic powder 2 and the binder were mixed to obtain a mixture. The amounts of the magnetic powder 2 and the binder were set so that the filling rate of the magnetic powder 2 in the final compound obtained was 15% by volume. Next, the obtained mixture was kneaded for 20 minutes using a Labo Plastomill (product name, Toyo Seiki Seisakusho Co., Ltd.) at a set temperature of 200°C and a rotation speed of 50 rpm to obtain a compound.
[0143] 2. Preparation of radio wave absorber The obtained compound was molded using a hot press under the conditions of molding pressure: 20 MPa, press temperature: 200°C, and press time: 10 minutes to obtain a sheet-shaped electromagnetic wave absorber (size: 100 mm x 100 mm). The amount of the compound used was set so that the thickness of the finally obtained electromagnetic wave absorber would be 4.5 mm.
[0144] Example 4 The same operations as in Example 3 were carried out to obtain a sheet-shaped radio wave absorber (size: 100 mm x 100 mm), except that the amounts of magnetic powder 2 and the binder were changed so that the filling rate of magnetic powder 2 in the final compound would be 30 volume %, and that the amount of compound used was changed so that the final radio wave absorber would have a thickness of 3 mm.
[0145] Comparative Example 6 The same operations as in Example 3 were carried out to obtain a sheet-shaped radio wave absorber (size: 100 mm x 100 mm), except that the amounts of magnetic powder 2 and the binder were changed so that the filling rate of magnetic powder 2 in the final compound was 40 volume %, and that the amount of compound used was changed so that the final radio wave absorber had a thickness of 2 mm.
[0146] Table 2 shows the “filling rate (unit: volume %) of the magnetic powder in the radio wave absorbing layer,” the “thickness (unit: mm) of the radio wave absorbing layer,” and “(P / 100)×Q” of each of the radio wave absorbers in Example 3, Example 4, and Comparative Example 6.
[0147] [measurement] 1. Measurement of transmission loss and return loss (1) The transmission attenuation (unit: dB) and return attenuation (unit: dB) of each of the radio wave absorbers of Examples 1 to 4 and Comparative Examples 1 to 6 were measured. Specifically, the measurements were carried out as follows. As measuring devices, a vector network analyzer (product name: N5225B) manufactured by Keysight and a horn antenna (product name: RH12S23) manufactured by Keycom Corporation were used, and S parameters were measured by the free space method with an incident angle of 0° and a sweep frequency of 60 GHz to 90 GHz, and the transmission attenuation and return loss at 76.5 GHz were obtained for the radio wave absorbers of Example 1, Example 2, and Comparative Examples 1 to 5, and the transmission attenuation and return loss at 85.0 GHz were obtained for the radio wave absorbers of Example 3, Example 4, and Comparative Example 6. The results are shown in Tables 1 and 2, respectively.
[0148] [Table 1]
[0149] [Table 2]
[0150] As shown in Tables 1 and 2, it was confirmed that the radio wave absorbers of Examples 1 to 4 each had a transmission loss and a return loss of 10 dB or more in the millimeter wave band. On the other hand, it was confirmed that in each of the wave absorbers of Comparative Examples 1 to 6, at least one of the transmission loss and the return loss was less than 10 dB.
[0151] [Preparation of radio wave absorber (3)] Example 5 1. Preparation of the compound A compound was prepared using magnetic powder 1 and a binder (product name: Mirastomer (registered trademark) 7030NS, olefin-based thermoplastic elastomer (TPO), Mitsui Chemicals, Inc.) Specifically, the compound was prepared as follows. The magnetic powder 1 and the binder were mixed to obtain a mixture. The amounts of the magnetic powder 1 and the binder were set so that the filling rate of the magnetic powder 1 in the final compound was 30 volume %. The mixture was then kneaded for 20 minutes using a Labo Plastomill (product name, Toyo Seiki Seisakusho Co., Ltd.) at a set temperature of 200°C and a rotation speed of 50 rpm to obtain a compound.
[0152] 2. Preparation of radio wave absorber The obtained compound was extruded into a cylindrical shape from a die using a twin-screw kneading extruder [model: KZW15TW, Technobel Co., Ltd.] with the screw temperature set at 200°C, to obtain a cylindrical radio wave absorber (circular inner diameter: 100 mm, height: 150 mm, thickness: 3 mm).
Claims
1. A radio wave absorber having a radio wave absorbing layer containing a magnetic powder and a binder, and not having a metal layer, The thickness of the radio wave absorbing layer is 10 mm or less, The magnetic powder includes magnetoplumbite hexagonal ferrite powder, the filling rate of the magnetic powder in the radio wave absorbing layer is 8 volume % or more and 35 volume % or less; A radio wave absorber that satisfies the relationship 0.65≦(P / 100)×Q, where P is a volume % of the filling rate of the magnetic powder in the radio wave absorbing layer and Q mm is a thickness of the radio wave absorbing layer.
2. 2. The radio wave absorber according to claim 1, wherein the thickness of the radio wave absorbing layer is 5 mm or less, and the filling rate is 15 volume % or more and 35 volume % or less.
3. 3. The radio wave absorber according to claim 1, wherein the magnetic powder contains a powder of magnetoplumbite-type hexagonal ferrite represented by the following formula (1): 【Chemistry 1】 In formula (1), A represents at least one metal element selected from the group consisting of Sr, Ba, Ca, and Pb, and x satisfies 1.5≦x≦8.
0.
4. 4. The radio wave absorber according to claim 3, wherein A in the formula (1) is Sr.
5. 5. The radio wave absorber according to claim 3, wherein x in the formula (1) satisfies 1.5≦x≦6.
0.
6. In the particle size distribution based on the number of particles measured by a laser diffraction scattering method, the most frequent value is the mode diameter, and the cumulative 10% diameter is the D 10 , and cumulative 90% diameter D 90 6. The radio wave absorber according to claim 1, wherein, when the mode diameter is 5 μm or more and less than 10 μm, and (D90-D10) / mode diameter≦3.
0.
7. A radio wave absorber described in any one of claims 1 to 6 having a sheet-like or film-like shape.
8. The radio wave absorber according to any one of claims 1 to 6, which has a three-dimensional shape.
9. A compound used in the manufacture of the radio wave absorber according to any one of claims 1 to 8, The magnetic material contains a magnetic powder and a binder, and the filling rate of the magnetic powder is 8% by volume or more and 35% by volume or less, The compound, wherein the magnetic powder comprises a powder of magnetoplumbite-type hexagonal ferrite.
Citation Information
Patent Citations
Electromagnetic wave absorbing body
JP1996340191A
Magnetic powder for use of wave absorber, its manufacturing method, and the wave absorber
JP2007250823A
Radio wave absorption sheet
JP2018056492A
Electromagnetic-wave-absorbing sheet
WO2018084234A1